5x-7(2x-3)=c

Simple and best practice solution for 5x-7(2x-3)=c equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-7(2x-3)=c equation:


Simplifying
5x + -7(2x + -3) = c

Reorder the terms:
5x + -7(-3 + 2x) = c
5x + (-3 * -7 + 2x * -7) = c
5x + (21 + -14x) = c

Reorder the terms:
21 + 5x + -14x = c

Combine like terms: 5x + -14x = -9x
21 + -9x = c

Solving
21 + -9x = c

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-21' to each side of the equation.
21 + -21 + -9x = -21 + c

Combine like terms: 21 + -21 = 0
0 + -9x = -21 + c
-9x = -21 + c

Divide each side by '-9'.
x = 2.333333333 + -0.1111111111c

Simplifying
x = 2.333333333 + -0.1111111111c

See similar equations:

| 42=8n-2n+12 | | 800l=2400 | | 10x+3=12x-3 | | 4-6v=2v+12 | | -9(y+7)-6(y-3)=o | | -3y+4+6y=16 | | 5x+11x-10+2x=6x+3x+7 | | 8x-(3x+2)=3x+12 | | 1/3-7/2=k/6 | | 5(3x+8)= | | 2(4+4v-10v)= | | 2(3+2x)=2(x-6) | | 65+90+50+80+x=180 | | 2w+2(600)=2400 | | -15+n=-22 | | 6-2(4+5)+6=-6 | | 6x-6(2x+7)=-90 | | -6-6(4r+7)=12-4r | | 1=r+3+4 | | -15=9-22 | | 1/4x-6=-5 | | 8-2x=2-x | | 5x+3(-6x+10)=-87 | | 3(4+4v-10v)= | | 1/6m=1/10-2/9 | | -2+4t-8=2 | | Y/4+1/5=7 | | 3m+4+6m=-14 | | -2(x+3)-5(x-4)=b | | -7(1-7m)=-7-4m | | 2t^2-4t+1=0 | | 600i=2400 |

Equations solver categories